Biological variations in a long-term ex situ cultivation: a Mediterranean demosponge as model system - DI BARI, G.; CARDONE, F.; GAINO, E.; LIUZZI, G. M.; NONNIS MARZANO, C.; SCOCCIA, F.; CORRIERO, G. (Mediterranean Marine Science, 2014)
The demosponge Tethya citrina Sarà & Melone was subjected to long-term aquarium farming, considering that several species belonging to this genus are a rich source of useful bioactive metabolites. The rearing method in the present research was mainly based on applying parameters taken from the current literature. The sponge's biological activity was assessed in terms of survival and growth over time; status of filtering apparatus; protein banding profiles. Farmed sponges showed a high survival rate and marked reduction in size. In addition, they were frequently affected by massive production of asexual buds. Histological and ultrastructural observations showed a gradual disorganization of the sponge choanocyte chambers, with a drastic reduction in choanocytes and a progressive increase in spherulous cells. Comparative electrophoretic analysis of the protein profiles of wild and reared specimens showed differences in protein composition and abundance between the tested groups. Such data are consistent with the increase in spherulous cells whose content was markedly electron-dense, a feature stressing the proteinaceous nature of these inclusions. Experimental tank-rearing of Tethya provided promising responses in terms of high survival rate of the species and easy reproduction, though the rearing protocol used led to profound morpho-functional changes in the sponge. This confirms the inadequate state of knowledge on farming techniques for this taxon, while also highlighting potential applications in biotechnology of ex situ breeding techniques, in order to modify the sponges' biological responses.